Matterhorn [compact disc, unabridged] : a novel of the Vietnam War - Marlantes, Karl (Blackstone Audio, 2010)
When young Waino Mellas, a Bravo Company lieutenant, is unceremoniously dropped into the jungle of Vietnam, he is instantly forced into manhood. Facing the horrors of war in Southeast Asia, Waino and his comrades embark on a long, torturous, bloody adventure, where the Vietnamese wilderness is just as dangerous as the enemy.